Pengaruh Gerakan Literasi Ruang Pojok Baca Sekolah Terhadap Minat Baca Peserta Didik Kelas IV SDN Bugangan 01 Kota Semarang - Putri, Ganenia Tristina Ulia; Utami, Rizky Esti; Agustini, Ferina; Badriyah, Siti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to find out how the school reading corner literacy movement is implemented on the reading interest of class IV students at SDN Bugangan 01, Semarang City. A quantitative approach was used in this research. In determining the sample, researchers used a non-probability sampling method. Observations were carried out with the aim of measuring the level of student involvement in using the reading corner, as well as assessing their reading interest and data collection techniques using questionnaires. The data analysis technique used in this research is descriptive. Based on the research results obtained from the implementation of the school reading corner literacy movement on the reading interest of class IV students at SDN Bugangan 01, Semarang City, the reading corner in class IV at SDN Bugangan 01 is in the good category. Likewise, the reading interest of class IV students in the Reading Corner at SDN Bugangan 01 and reading interest increased along with the presentation interval, reaching 64.5% in the good category